Trends in "avoidable" mortality by neighbourhood income in urban Canada from 1971 to 1996 - James, Paul Damien (University of Ottawa (Canada), 2003)
Objective. To examine changes in neighbourhood income-related differences in 'avoidable', and other cause, mortality in urban Canada from 1971 to 1996. Data source. Canadian Mortality Database and population censuses for 1971, 1986, 1991 and 1996. The deaths were coded to census tract and grouped into neighbourhood income quintiles. Methods. Deaths were classified as amenable to medical or public health interventions according to seven selected classification lists. Age-standardized period expected years of life lost (SEYLL) were calculated. Quintile differentials were determined using rate ratios and rate differences. Results. From 1971 to 1996, the avoidable SEYLL differences between the richest and poorest quintiles diminished 58.5--72.1% for men and 56.4--82.2% for women, depending on the classification list considered. The SEYLL differences relating to other causes increased 8.0% in men and decreased 0.5% in women. Conclusion. Deaths amenable to medical and public health interventions contributed to reducing socioeconomic mortality disparities in urban Canada.
Keywords: Health Sciences, Public Health.; Sociology, Public and Social Welfare.; Sociology, Demography.